Association of serum bilirubin levels with development and progression of albuminuria, and decline in estimated glomerular filtration rate in patients with type 2 diabetes mellitus. Issue 2 (16th September 2013) - Toya, Kiwako; Babazono, Tetsuya; Hanai, Ko; Uchigata, Yasuko
Abstract Aims/Introduction Recent observational studies suggest elevated levels of bilirubin, an endogenous anti‐oxidant, might protect against kidney disease. We carried out an observational cohort study to assess whether higher baseline levels of bilirubin, within normal range, could predict the rate of development and progression of diabetic nephropathy in patients with type 2 diabetes. Materials and Methods Japanese type 2 diabetic patients with normo‐ or microalbuminuria and normal serum bilirubin (<1.2 mg/dL) were recruited from a single center, and categorized according to baseline serum bilirubin levels. Two independent end‐points were specified: development or progression of diabetic nephropathy, based on transition to a more advanced stage of albuminuria (albuminuria cohort), and the rate of change in estimated glomerular filtration rate (eGFR cohort). Results Albuminuria and eGFR cohorts were constructed consisting of 1, 915 patients and 1, 898 patients, respectively, with 1, 738 patients overlapping. Mean follow up was 4.4 and 5.4 years for the two cohorts, respectively. Within the albuminuria cohort, 132 (9%) of 1, 418 patients with normoalbuminuria developed microalbuminuria, and 56 (11%) of 497 patients with microalbuminuria developed macroalbuminuria. Higher baseline bilirubin levels were associated with significantly lower risk of progression from microalbuminuria to macroalbuminuria in both the univariate and multivariate analyses. In normoalbuminuric patients, an inverse association was found when restricted to a subgroup with elevated hemoglobin A1c levels. There was no relationship between bilirubin levels and the rate of change in eGFR. Conclusions Higher serum bilirubin levels, within normal range, might be predictive of a lower risk of progression of nephropathy in type 2 diabetic patients.